Fault-Diagnosis Systems An Introduction from Fault Detection to Fault Tolerance - Isermann, Rolf.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Supervision, health-monitoring, fault detection, fault diagnosis and fault management play an increasing role for technical processes and vehicles, in order to improve reliability, availability, maintenance and life-time. For safety-related processes fault-tolerant systems with redundancy are required in order to reach comprehensive system integrity. This book gives an introduction into the field of fault detection, fault diagnosis and fault-tolerant systems with methods which have proven their performance in practical applications. It guides the reader in a structured tutorial style: supervision methods, reliability, safety, system integrity and related terminology; fault detection with signal-based methods for periodic and stochastic signals; fault detection with process model-based methods like parameter estimation, state estimation, parity equations and principal component analysis; fault diagnosis with classification and inference methods; fault-tolerant systems with hardware and analytical redundancy; many practical simulation examples and experimental results for processes like electrical motors, pumps, actuators, sensors and automotive components; end-of-chapter exercises for self testing or for practice. The book is dedicated to graduate students of electrical, mechanical, chemical engineering and computer science and for practising engineers.
Fundamentals -- Supervision and fault management of processes — tasks and terminology -- Reliability, Availability and Maintainability (RAM) -- Safety, Dependability and System Integrity -- Fault-Detection Methods -- Process Models and Fault Modelling -- Signal models -- Fault detection with limit checking -- Fault detection with signal models -- Fault detection with process-identification methods -- Fault detection with parity equations -- Fault detection with state observers and state estimation -- Fault detection of control loops -- Fault detection with Principal Component Analysis (PCA) -- Comparison and combination of fault-detection methods -- Fault-Diagnosis Methods -- Diagnosis procedures and problems -- Fault diagnosis with classification methods -- Fault diagnosis with inference methods -- Fault-Tolerant Systems -- Fault-tolerant design -- Fault-tolerant components and control -- Application Examples -- Fault detection and diagnosis of DC motor drives -- Fault detection and diagnosis of a centrifugal pump-pipe-system -- Fault detection and diagnosis of an automotive suspension and the tire pressures.
Keywords: Control engineering; Robotics; Mechatronics; Quality control; Reliability; Industrial safety; Computational complexity; Control and Systems Theory; Control, Robotics, Mechatronics; Quality Control, Reliability, Safety and Risk; Complexity